Cooperative Ability as a Moderator of Modeling Effects on Preschooler’s Pattern Recognition Skills - Rachman, Nabila; Sujatmiko, Muhammad Adi Nugroho; Jamaluddin, Muhammad; dos Reis, Dulce Elda Ximenes (Jurnal Psikologi Teori dan Terapan, 2025)
Background: This research explores how modeling as a learning strategy can support preschool children in recognizing patterns, and whether their cooperative skills influence this effect. Objective: This study aimed to examine the effect of modeling as a learning strategy on pattern recognition skills in preschoolers and to determine whether cooperative ability acts as a moderator. Method: Using a quasi-experimental design with pretest and posttest, the study involved 31 preschool children aged 4–5 years, 17 boys and 14 girls from a private kindergarten in East Java. The participants were divided equally into an experimental group and a control group. Measurements were conducted using validated pattern recognition skills and cooperative ability, and the data were analyzed using independent t-tests and ANOVA. Results: revealed that preschool children in the experimental group showed a significantly higher improvement in pattern recognition (p < 0.001). Conclusion: Furthermore, cooperation was found to strengthen the relationship between modeling and pattern recognition. These findings highlight the importance of combining cognitive learning strategies with social skill development in early preschool education. Abstrak Latar Belakang: Penelitian ini mengeksplorasi bagaimana pemodelan sebagai strategi pembelajaran dapat mendukung anak-anak prasekolah dalam mengenali pola, dan apakah keterampilan kooperatif mereka memengaruhi efek ini. Tujuan: Penelitian ini bertujuan untuk menguji pengaruh pemodelan sebagai strategi pembelajaran terhadap keterampilan pengenalan pola pada anak-anak prasekolah dan untuk menentukan apakah kemampuan kooperatif bertindak sebagai moderator. Metode: Menggunakan desain kuasi-eksperimental dengan pretes dan posttes, penelitian ini melibatkan 31 anak prasekolah berusia 4–5 tahun, 17 laki-laki dan 14 perempuan dari taman kanak-kanak swasta di Jawa Timur. Peserta dibagi secara merata menjadi kelompok eksperimen dan kelompok kontrol. Pengukuran dilakukan dengan menggunakan keterampilan pengenalan pola dan kemampuan kooperatif yang tervalidasi, dan data dianalisis menggunakan uji-t independen dan ANOVA. Hasil: mengungkapkan bahwa anak-anak prasekolah dalam kelompok eksperimen menunjukkan peningkatan yang signifikan lebih tinggi dalam pengenalan pola (p < 0,001). Kesimpulan: Lebih jauh, kerja sama ditemukan untuk memperkuat hubungan antara pemodelan dan pengenalan pola. Temuan ini menyoroti pentingnya menggabungkan strategi pembelajaran kognitif dengan pengembangan keterampilan sosial dalam pendidikan prasekolah awal.